2019
DOI: 10.1002/ep.13302
|View full text |Cite
|
Sign up to set email alerts
|

Improving CO2/CH4 and CO2/N2 adsorptive selectivity of Cu‐BTC and MOF‐derived nanoporous carbon by modification with nitrogen‐containing groups

Abstract: For the first time in this study compared the adsorption capacity and selectivity of carbon dioxide (CO 2), methane (CH 4), and nitrogen (N 2) on amine-modified copper(II) benzene-1,3,5-tricarboxylate (Cu-BTC) and metal organic framework-derived nanoporous carbon (MOF/NPC) by employing a volumetric measurement. The MOF/NPC is synthesized via direct carbonization of the Cu-BTC as a template without any carbon precursor at 900 C under N 2 atmosphere and shows easy synthesis, large surface area, high excellent th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This simple interaction has so far led to a number of nanoporous polymers in which nitrogen-rich functions are incorporated, such as triazine, 65,66 tetrazole, 67 imidazole, 68,69 imide 70 and amines. 42,71 Increased CO 2 adsorption capacity in UPJS-13 (FD) and UPJS-14 (FD) can be explained by an interaction between CO 2 molecules and adsorption sites represented by a lone pair on the azo functional groups located in the molecular structure of the MTA linker. In the case of azo group, the interaction with CO 2 was also conrmed by computational studies, in which the relative binding affinity of CO 2 to the -N]Ngroup using trans-azobenzene as a model system were performed.…”
Section: Solid-state Nmr Spectroscopymentioning
confidence: 99%
“…This simple interaction has so far led to a number of nanoporous polymers in which nitrogen-rich functions are incorporated, such as triazine, 65,66 tetrazole, 67 imidazole, 68,69 imide 70 and amines. 42,71 Increased CO 2 adsorption capacity in UPJS-13 (FD) and UPJS-14 (FD) can be explained by an interaction between CO 2 molecules and adsorption sites represented by a lone pair on the azo functional groups located in the molecular structure of the MTA linker. In the case of azo group, the interaction with CO 2 was also conrmed by computational studies, in which the relative binding affinity of CO 2 to the -N]Ngroup using trans-azobenzene as a model system were performed.…”
Section: Solid-state Nmr Spectroscopymentioning
confidence: 99%
“…Figure 3 For practical purposes, the performance evaluation metrics used for the screening should, in principle, correlate with the performance of MOFs in the actual PSA and VSA processes. For binary gas separation cases, the selectivity and working capacity have been used frequently in the literature [37,38,39], but recent studies have shown that these commonly used metrics do not necessarily reflect the performance of MOFs at the process-level [40,41,42,32]. We adopted an ideal VSA/PSA process simulation method to quickly evaluate the performance of MOFs at the process-level.…”
Section: Decision Variablementioning
confidence: 99%
“…Recently, metal-organic frameworks (MOFs) have been gaining attention for their potential application in gas separation owing to their inherent properties, such as high specific surface area, large porosity, and tunable pore size [8,9]. In the literature, MOFs have been extensively studied for their capability to separate CO 2 from CH 4 [10][11][12]. Amongst the materials investigated, HKUST−1 has been identified as a good candidate for CO 2 /CH 4 separation because of its good CO 2 /CH 4 selectivity [13,14].…”
Section: Introductionmentioning
confidence: 99%